Alternatives to vivisection: Scanning technologies replace and complement invasive autopsies. (22nd May 2019) - Hunter, Philip
Abstract : Scanning and other non‐invasive technologies not only help to address relatives' concerns over invasive autopsy, but can even yield more information about the cause of death when used in combination.